Consecuencias Psicosociales Actuales De Mujeres Estudiantes De La Universidad Antonio Nariño Que Fueron Víctimas De Abuso Sexual Durante Su Infancia (2019)
This research is carried out with the objective of identifying what are the current psychological consequences that affect the adult life of 4 female students of last semesters of psychology at the Antonio Nariño University who suffered sexual abuse during their childhood. To achieve the general objective, we worked from the qualitative methodology, corresponding to an exploratory study, with narrative design and data collection technique, open interviews were used.